2007
DOI: 10.1177/1470595807075179
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Challenges Confronted when Conducting Management Research in China

Abstract: This article addresses some fundamental methodological issues confronting management researchers undertaking research in China. Among other things, it considers the following: cultural factors that might impact on what is a researchable question; sampling issues; difficulties in developing valid research instruments; problems pertaining to data collection; and the challenges of data interpretation. While the issues are by no means unique to China, there are a number of matters that require special attention in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 93 publications
2
65
0
1
Order By: Relevance
“…Researchers also need to account for larger than average random segments by accordingly increasing their original sample size. Although a considerable share of randomly choosing respondents was observed, the indirect preference elicitation through choicebased conjoint experiments allowed considerably stronger differentiation than direct importance ratings, where consumers tend to find all quality cues similarly important, confirming previously voiced concerns over problems with acquiescence bias when conducting consumer research in China (Harzing et al, 2012;Stening & Zhang, 2007). Choice-based conjoint experiments with graphical product simulations revealed a stronger importance of intrinsic quality cues such as packaging and fat content than suggested by direct importance ratings.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Researchers also need to account for larger than average random segments by accordingly increasing their original sample size. Although a considerable share of randomly choosing respondents was observed, the indirect preference elicitation through choicebased conjoint experiments allowed considerably stronger differentiation than direct importance ratings, where consumers tend to find all quality cues similarly important, confirming previously voiced concerns over problems with acquiescence bias when conducting consumer research in China (Harzing et al, 2012;Stening & Zhang, 2007). Choice-based conjoint experiments with graphical product simulations revealed a stronger importance of intrinsic quality cues such as packaging and fat content than suggested by direct importance ratings.…”
Section: Discussionsupporting
confidence: 56%
“…Use of self-reported importance may be problematic in a country like China, as cross-cultural research has shown that high power distance in a country is related to more acquiescence bias (Harzing, Köster, & Zhao, 2012), and response style issues have previously been identified as one of the problems faced when conducting this type of research in China (Stening & Zhang, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While research in Chinese markets has grown in popularity in recent years, data collection in China is a notoriously difficult task (Stening & Zhang 2007). Yeung (1995, p. 317) called it the problem of 'getting in,' and noted that opportunism and persistence were necessary if access were to be gained.…”
Section: Methodsmentioning
confidence: 99%
“…Where Western researchers strive for parsimony and generalisability in their concept definitions, the Chinese are comfortable with complex definitions that reflect reality (Stening & Zhang 2007). This is referred to by Fang (1999Fang ( , 2006 as the Chinese paradox, and is embedded in cultural values such as yin-yang, where two opposing views can combine synergistically to create a richer composite.…”
Section: Trust In the Chinese Contextmentioning
confidence: 99%
“…The interviews with Chinese managers and experts were conducted in Mandarin (89%), and the ones with English speaking executives were conducted in English (11%). The interviews lasted up to 2 h each and were not tape-recorded, because this would have inhibited interviewees' readiness to speak openly, particularly in China (see Tsang, 1998;Stening and Zhang, 2007;Gamble, 2010;Siebers, 2011). The interviews were transcribed directly by the author during the interview.…”
Section: Data Collection and Analysismentioning
confidence: 99%